Motor Point Stimulation in Spinal Paired Associative Stimulation can Facilitate Spinal Cord Excitability - Fok, Kai Lon; Kaneko, Naotsugu; Sasaki, Atsushi; Nakagawa, Kento; Nakazawa, Kimitaka; Masani, Kei (Frontiers in Human Neuroscience, 2020)
Paired associative stimulation at the spinal cord (spinal PAS) has been shown to increase muscle force and dexterity by strengthening the corticomuscular connection, through spike timing dependent plasticity. Typically, transcranial magnetic stimulation (TMS) and transcutaneous peripheral nerve electrical stimulation (PNS) are often used in spinal PAS. PNS targets superficial nerve branches, by which the number of applicable muscles is limited. Alternatively, a muscle can be activated by positioning the stimulation electrode on the “motor point” (MPS), which is the most sensitive location of a muscle to electrical stimulation. Although this can increase the number of applicable muscles for spinal PAS, nobody has tested whether MPS can be used for the spinal PAS to date. Here we investigated the feasibility of using MPS instead of PNS for spinal PAS. Ten healthy male individuals (26.0±3.5 yrs) received spinal PAS on two separate days with different stimulation timings expected to induce (1) facilitation of corticospinal excitability (REAL) or (2) no effect (CONTROL) on the soleus. The motor evoked potentials (MEP) response curve in the soleus was measured prior to the spinal PAS, immediately after (0 minute) and at 10, 20, 30 minutes post-intervention as a measure of corticospinal excitability. The post-intervention MEP response curve areas were larger in the REAL condition than the CONTROL conditions. Further, the post-intervention MEP response curve areas were significantly larger than pre-intervention in the REAL condition but not in the CONTROL condition. We conclude that MPS can facilitate corticospinal excitability through spinal PAS.